Enhancing the overall thermal performance of a large aperture parabolic trough solar collector using wire coil inserts. (June 2020) - Yılmaz, İbrahim Halil and Mwesigye, Aggrey and Göksu, Taha Tuna
Highlights: Use of wire coil inserts in a high concentration ratio parabolic trough solar collector is investigated. Improvement in the thermal efficiency and thermodynamic performance are demonstrated. The thermal efficiency increases by up to 1.4% for flow rates lower than 13 m 3 /h. New correlations for the Nusselt number and friction factor are derived and presented. Significant reductions in the entropy generation rates by up to 100% are shown. Abstract: With the use of large apertures (higher concentration ratios) in parabolic trough solar collectors, increased temperature gradients, increased heat losses and increased heat transfer irreversibilities become inevitable. As such, means of reducing the magnitude of these operating parameters to enhance the overall thermal and thermodynamic performances become crucial. In this study, the use of wire coil inserts in the receiver's absorber tube to improve the parabolic trough solar collector's performance and to lessen the associated temperature gradients is presented. The parabolic trough solar collector having an aperture width of 9 m and a rim angle of 80° was modeled. Using Monte-Carlo ray tracing, the realistic heat flux profile on the receiver's absorber tube was obtained. The resulting non-uniform heat flux profile was later coupled to a finite volume based computational fluid dynamics model. The working fluid properties were considered to be temperature-dependent. The wire coil inserts with a pitch of 0.076, 0.114 and 0.152 m and widths of 0.03, 0.033 and 0.036 m were examined in this study. The wire coil has a triangular cross-section of 0.0076 m in size. Results show significant improvements in receiver thermal performance with the use of wire coil inserts owing to the improved fluid mixing, disruption of the thermal boundary layer and reduction in the absorber tube temperatures. The heat transfer performance is increased up to 183% whereas the thermal efficiency improves between 0.4 and 1.4% when the flow rate is below 13 m 3 /h.